PROBABILITY ANALYSIS ON LAST PLY FAILURE OF COMPOSITE LAMINATES BASED ON UNIVERSAL GENERATING FUNCTION METHOD - LIU ChengLong; ZHOU JinYu; QIU Rui; ZHUANG BaiLiang; HU Jian (Jixie qiangdu)
The reliability of composite laminates is analyzed by universal generating function method. Load,strength parameters universal generating function,complex operators and the corresponding performance structure functions are defined,the resistance of the single layer,resistance sequences and system resistance universal generating function are constructed respectively. The reliability analysis model of laminates is established based on the last ply failure criterion. In the complex operation of universal generating function, K-means clustering and like terms collecting techniques are used to reduce computational costs and improve efficiency. This method is applicable to the reliability assessment of structural systems,in which there are many random variables（ including non-normal random variables）,the performance function is non-linear,and failure correlation between resistance sequences of laminates that contain common failure elements and failure elements within the resistance sequences due to sharing the same random load source is considered. Two examples are given. The reliability value is close to the Monte Carlo simulation results. The new method can provide a new idea for reliability analysis of composite laminates.